Efektivitas Pajak Daerah Terhadap Pendapatan Asli Daerah - Kurnia; Apriliani, Ragita (Owner : Riset dan Jurnal Akuntansi, 2024)
Regional Original Revenue (PAD) is a necessary source of revenue for the region. The largest revenue from PAD comes from local taxes including street lighting tax, billboard tax and PBB-P2 which is used to implement regional autonomy over decentralization. The purpose of this study is to determine the efficiency and effect of street lighting tax, billboard tax and PBB-P2 on PAD in Bandung City. The approach and data used in this study are quantitative approaches and secondary data obtained at BAPENDA in the form of Regional Budget Realization Reports (LRAPBD) with a total of 60 research samples from January to December 2017-2021. The analysis technique used is multiple linear regression analysis through SPSS 26 Version 26 software. The results revealed that the effectiveness of street lighting, billboard tax and PBB-P2 tax revenues from 2017 to 2021 showed that the level of effectiveness was included in the effective category, indicating that the tax received had reached the target. Simultaneously, all variables affect PAD. Partially, the street lighting tax and PBB-P2 have no effect on PAD, while the billboard tax has no effect on PAD.